PEMBERDAYAAN EDUKATIF DAN INOVASI LINGKUNGAN DI DESA HILIGANOITA, KECAMATAN BAWOLATO - Anugrah Laia; Happy Juliaman Gulo; Martiana Putri Jelita Ndruru; Albinus Gulo; Epiyanus Lase; Rama Meiman Tafonao; Elintan Fatemaluo; Elvin Reslina Gea; Priska Zendrato; Semangat Hati Hulu; Sesuaikan Sarumaha (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
Educational empowerment and environmental innovation in Hiliganoita Village, Bawolato District, represent efforts to increase community participation aimed at improving village quality, based on the potential of existing human resources. This activity was carried out through the Community Service Program (KKN), which serves as a form of student engagement in community development and aims to foster student empathy toward social and environmental conditions. Prior to determining the work programs, initial activities such as observation, interviews, and discussions were conducted with local residents to identify relevant needs. The outcomes of this program included: (1) Private tutoring, (2) Utilization of bamboo for waste bins, (3) Maintenance of cleanliness and beauty of village facilities and the environment, (4) Construction of dishwashing stations, and (5) Installation of street signs. All activities were implemented over approximately 40 days and were successfully executed with clear alignment to community needs. This program not only provided direct benefits to the local community but also strengthened collaboration between students and residents through active participation and shared responsibility.